Choroid, Haller's, and Sattler's Layer Thickness in Intermediate Age-Related Macular Degeneration With and Without Fellow Neovascular Eyes - Esmaeelpour, Marieh (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. To analyze choroidal, Sattler's, and Haller's layer thickness maps in age-related macular degeneration (AMD) patients having eyes with bilateral large drusen and pigment changes (intermediate AMD), in patients having intermediate AMD eyes with neovascular fellow eyes (nAMD), and in healthy subjects using three-dimensional (3D) 1060-nm optical coherence tomography (OCT). METHODS. Automatically generated choroidal thickness (ChT), retinal thickness, and Sattler's and Haller's layer thickness maps were statistically analyzed in 67 subjects consisting of intermediate AMD (n = 21), intermediate AMD (n = 22) with fellow nAMD eyes (n = 22), and healthy eyes (n = 24) with no age and axial eye length difference between groups of eyes (P > 0.05, ANOVA). Eyes were imaged by a prototype high-speed (60,000 A-scans/s) spectral-domain 3D 1060-nm OCT over a 36° × 36° field of view. RESULTS. The mean ± SD (μm) subfoveal ChT for healthy subjects and for bilateral intermediate AMD, unilateral intermediate AMD, and their nAMD fellow eyes was 259 ± 95 and 222 ± 98, 149 ± 60, and 171 ± 78, respectively. Choroidal thickness maps demonstrated significant submacular thinning in unilateral intermediate AMD in comparison to healthy and bilateral intermediate AMD eyes (P < 0.001, ANOVA, post hoc P < 0.001 and P < 0.05, respectively). Sattler's and Haller's layers were thinnest in intermediate AMDs that presented with nAMD fellow eyes (Kruskal-Wallis test P < 0.01). For the choroid and its sublayers, there was no difference between the intermediate AMD eyes and their fellow nAMD eyes (paired testing, P < 0.05). CONCLUSIONS. The 3D 1060-nm OCT choroidal imaging visualized significant changes in choroidal, Sattler's, and Haller's layer thickness in relation to the progression of AMD. This may be important for understanding the choroidopathy in the pathophysiology of AMD.